The Development of Problem-Based Learning Model E-Module Integrated with Multiculturalism in Elementary Schools - Desyandri, Desyandri; Agustina, Yana; Lusiana, Dewi (Jurnal Prima Edukasia, 2024)
The absence of technological teaching materials tailored to each local area's specific conditions served as the impetus for this research. The objective of this research is to generate e-modules that are both practical and valid as educational resources. This study employs the five stages of ADDIE development research: analysis, design, development, implementation, and evaluation. The research results indicate that the e-module developed by the researchers achieved a score of 89% for material expert validators, 86% for media expert validators, and 84% for language expert validators, all of which are classified as "very valid" 91.5% and 92% of the practical results for teachers and pupils regarding the companion e-module were achieved with very practical criteria. The companion e-module with the Problem-Based Learning (PBL) multicultural-based model that has been developed fulfils the valid criteria and is practical to use as teaching material, as can be inferred from these results. Based on these findings, this instructional material can serve as an innovative tool to assist educators in the classroom learning process.